2011
DOI: 10.1186/1471-2180-11-242
|View full text |Cite
|
Sign up to set email alerts
|

Niche differentiation of two sympatric species of Microdochium colonizing the roots of common reed

Abstract: BackgroundFungal endophyte communities are often comprised of many species colonizing the same host. However, little is known about the causes of this diversity. On the one hand, the apparent coexistence of closely related species may be explained by the traditional niche differentiation hypothesis, which suggests that abiotic and/or biotic factors mediate partitioning. For endophytes, such factors are difficult to identify, and are therefore in most cases unknown. On the other hand, there is the neutral hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 54 publications
(68 reference statements)
0
15
0
Order By: Relevance
“…The phylogenetic relationship estimation using the ML method and HKY85 matrix system is also a good strategy for robust and high-quality tree constructions based on ribosomal genes [79]. Having said that, phylogenies obtained using ML/HKY85 have also been employed to establish taxonomic inferences in bacteria [80], fungi [81,82] and plants [83]. Finally, a phylogeny based on 18S rRNA gene was constructed and demonstrated that TS11 is related with Emericellopsis spp.…”
Section: Resultsmentioning
confidence: 99%
“…The phylogenetic relationship estimation using the ML method and HKY85 matrix system is also a good strategy for robust and high-quality tree constructions based on ribosomal genes [79]. Having said that, phylogenies obtained using ML/HKY85 have also been employed to establish taxonomic inferences in bacteria [80], fungi [81,82] and plants [83]. Finally, a phylogeny based on 18S rRNA gene was constructed and demonstrated that TS11 is related with Emericellopsis spp.…”
Section: Resultsmentioning
confidence: 99%
“…Microdochium species are known as snow molds, and some are pathogenic to plants [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Microdochium nivale and Microdochium majus are two of the main causative agents of Fusarium head blight [ 42 ], whereas Microdochium lycopodinum and Microdochium phragmitis were isolated from plants without causing disease [ 45 , 46 ]. M. phragmitis was endophytic in common reed and was more present in flooded habitats than the closely related Microdochium bolleyi [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The members of the genus Microdochium are important plant pathogens, particularly on grasses and cereals. Some of the species of Microdochium are terrestrial cause economic damage to important plants [38,39], nonpathogenic, and also sometimes endophytes [40]. Many species of Microdochium were also identified in the aquatic (marine) environment after evaluating diseased as well as healthy salmon eggs and have been reported as M. lycopodinum and M. phragmitis [41].…”
Section: Discussionmentioning
confidence: 99%